The lost generation - Abd Razak, Dzulkifli (2006)
ON Dec 26, 2005, we recalled the first tragic anniversary of the Asian tsunami. While some are finding their way to normalcy, there are many others who are still struggling. This is not due to a lack of effort, aid or selfhelp. It is just that the impact of the tragedy was too devastating. Indeed, a tremor that occurred recently, albeit a milder one, still sent chills down the spine of many people in Aceh. Then there was the massive earthquake, measuring 7.6 on the Richter scale, which hit Pakistan, Afghanistan and northern India exactly three months ago on Oct 8 in South Asia. The earthquake caused widespread destruction in northern Pakistan. Twentyeight aftershocks occurred with a magnitude greater than 5.0 during the four days after the principal quake.